Evaluation of Inventory Policies for High-Turnover Medical Supplies in Tertiary Healthcare Centers in Remote Areas - Gutiérrez Yepes, Daniel Andrés (2024)
This study aimed to evaluate an inventory policy for high-turnover medical supplies in tertiary healthcare centers located in areas with difficult access. The research was applied in nature, featuring a non-experimental design, descriptive scope, and quantitative approach. A clinic in the municipality of Leticia, a region in Colombia known for its challenging access, was selected as the case study. Stochastic scenarios were assessed in comparison with the clinic’s current context, utilizing the stochastic (S, T) method as it met the necessary characteristics for the healthcare center. The results concluded that this method significantly optimizes costs, primarily due to variations in policy parameters such as economic order quantity, order frequency, safety stock, and service satisfaction levels.